A Review of the Role of Aahara for Children’s Health and Well-being - Kumari, Shiksha; Sankhian, Kushal; Bhushan, Bharat (International Research Journal of Ayurveda & Yoga, 2025)
Optimal nutrition during childhood is critical for growth, cognitive development, immunity, and overall well being. The first 1000 days – from conception to 2 years – represent a sensitive period where nutrient adequacy profoundly influences long-term health outcomes. Despite global efforts, malnutrition remains a major public health challenge, with millions of children affected by stunting, wasting, and underweight conditions. In India, childhood undernutrition continues to be a significant concern, underscoring the need for effective interventions. Ayurvedic principles emphasize an age-appropriate and balanced diet (Aahara) as central to child health. Classical texts, including the Kashyapa Samhita, recommend exclusive breastfeeding during the first 6 months, followed by the gradual introduction of complementary and solid foods tailored to the child’s constitution, digestive strength, and environmental factors. Proper nourishment supports body tissues (Dhatus), vital energy (Ojas), and Dosha balance, while preventing deficiencies and disease. This review integrates Ayurvedic dietary principles with contemporary nutritional guidelines, highlighting the role of parents, families, schools, and communities in promoting healthy eating behaviors. Ensuring balanced nutrition during childhood lays the foundation for lifelong physical, cognitive, and emotional well-being.